Myocardial Ischemia Assessment in Chronic Kidney Disease: Challenges and Pitfalls - Parnham, Susie F. C.; Gleadle, Jonathan M.; De Pasquale, Carmine G.; Selvanayagam, Joseph B. (Frontiers in Cardiovascular Medicine, 2014)
Coronary artery disease is the leading cause of mortality and morbidity in the chronic kidney disease (CKD) population and often presents with atypical symptoms. Current diagnostic investigations of myocardial ischemia in CKD lack sensitivity and specificity or may have adverse effects. We present a case vignette and explore the challenges of diagnostic myocardial stress investigation in patients with CKD.